EKSPERIMENTASI MODEL PROBLEM BASED LEARNING, THINK ALOUD PAIRS PROBLEM SOLVING DAN GROUP INVESTIGATION DENGAN PENDEKATAN SAINTIFIK DITINJAU DARI KONSEP DIRI DAN KREATIVITAS BELAJAR SISWA TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SMP - Aulia Ar Rakhman Awaludin; Mardiyana Mardiyana; Isnandar Slamet (Universitas Sebelas Maret, 2015)
Abstract: This research aims to know the different effect among learning model used i.e. Problem Based Learning, Think Aloud Pairs Problem Solving and Group Inverstigation models with scientific approach observed from students self concept and study creativity towards the ability of mathematics problem solving. This research used quasi experimental study with factorial design 3x2x3. The population of this research was the eighth grade student of State Junior High School of District Sragen Year of 2014/2015. The sampling technique used was stratified cluster random sampling. The data analysis used a three way analysis of variance with different cell at significance level of 0.05. The results of this research are : (1) PBL-S produces the same students ability of mathematics problem solving with TAPPS-S. Moreover, both produce the better students ability than GI-S. (2) Students with positive category of self concept produce the better ability of mathematics problem solving than students with negative category. (3) Students with high study creativity category produce the better ability of mathematics problem solving than the medium and low category. However, the students with medium and low study creativity category produce the same ability of mathematics problem solving. (4) In each learning models, both the students with positive and negative self concept have the same ability of mathematics problem solving. (5) In PBL-S and GI-S models, students with high, medium and low creativity have the same ability of mathematics problem solving. However, there is different ability between high and low creativity category in TAPPS-S model. (6) Students with positive and negative self concept have the same ability of mathematics problem solving in all study creativity categories (high, medium, low category). (7) At each learning models, students with positive and negative self concept and with high, medium and low creativity have the same ability of mathematics problem solving.Keywords : PBL, TAPPS, GI, Scientific Approach, Self Concept, Learning Creativity.